2021
DOI: 10.3389/fcell.2020.615698
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Peptide Modifications Reveal Direct and Indirect Roles of Hedgehog Morphogen Cholesteroylation

Abstract: Hedgehog (Hh) morphogens are involved in embryonic development and stem cell biology and, if misregulated, can contribute to cancer. One important post-translational modification with profound impact on Hh biofunction is its C-terminal cholesteroylation during biosynthesis. The current hypothesis is that the cholesterol moiety is a decisive factor in Hh association with the outer plasma membrane leaflet of producing cells, cell-surface Hh multimerization, and its transport and signaling. Yet, it is not decided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 72 publications
3
10
0
Order By: Relevance
“…Non-essential roles of the N-palmitate for Hh signaling activation on receiving cells can be further supported by in vitro assays that compare dually lipidated Shh (detergent-extracted from the cell membrane of Shh expressing cells, R&D 8908-SH), as used to generate cryo-EM structures that show lipid involvement, [33,34] and Shh released This reveals that dually lipidated R&D 8908-SH is unlike Shh after its release from Disp-and Scube2-expressing cells. This is also directly confirmed by reverse-phase high-performance liquid chromatography (RP-HPLC) analyses of their different hydrophobicities [17,18] : While R&D 8908-SH and cellular Shh elute in late fractions from the C4 column, consistent with their dual lipidation, Disp/Scube2-solubilized Shh elutes earlier and similar to an unlipidated N-truncated Δ25-38 ShhN control [17] (Figure 2E-F). As observed earlier, immunoblotting revealed that palmitoylation-deficient but cholesteroylated C25A Shh was also released as partially processed (Figure 2D, upper band) and Ntruncated proteins (Figure 2D, lower band).…”
Section: Hh Palmitoylation By Hhat Potentiates Signalingsupporting
confidence: 56%
See 4 more Smart Citations
“…Non-essential roles of the N-palmitate for Hh signaling activation on receiving cells can be further supported by in vitro assays that compare dually lipidated Shh (detergent-extracted from the cell membrane of Shh expressing cells, R&D 8908-SH), as used to generate cryo-EM structures that show lipid involvement, [33,34] and Shh released This reveals that dually lipidated R&D 8908-SH is unlike Shh after its release from Disp-and Scube2-expressing cells. This is also directly confirmed by reverse-phase high-performance liquid chromatography (RP-HPLC) analyses of their different hydrophobicities [17,18] : While R&D 8908-SH and cellular Shh elute in late fractions from the C4 column, consistent with their dual lipidation, Disp/Scube2-solubilized Shh elutes earlier and similar to an unlipidated N-truncated Δ25-38 ShhN control [17] (Figure 2E-F). As observed earlier, immunoblotting revealed that palmitoylation-deficient but cholesteroylated C25A Shh was also released as partially processed (Figure 2D, upper band) and Ntruncated proteins (Figure 2D, lower band).…”
Section: Hh Palmitoylation By Hhat Potentiates Signalingsupporting
confidence: 56%
“…This reveals that dually lipidated R&D 8908‐SH is unlike Shh after its release from Disp‐ and Scube2‐expressing cells. This is also directly confirmed by reverse‐phase high‐performance liquid chromatography (RP‐HPLC) analyses of their different hydrophobicities [ 17,18 ] : While R&D 8908‐SH and cellular Shh elute in late fractions from the C4 column, consistent with their dual lipidation, Disp/Scube2‐solubilized Shh elutes earlier and similar to an unlipidated N‐truncated Δ25‐38 ShhN control [ 17 ] (Figure 2E‐F). As observed earlier, immunoblotting revealed that palmitoylation‐deficient but cholesteroylated C25A Shh was also released as partially processed (Figure 2D, upper band) and N‐truncated proteins (Figure 2D, lower band).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations